Feasibility of 25kw parabolic dish - sterling engine based concentrating solar power under Malaysia environment - Affandi, Rosnani; Omar, Zamali; Ruddin Ab. Ghani, Mohd; Chin Kim, Gan (International Journal of Engineering & Technology, 2018)
The feasibility study is to ensure that the implementation of the Parabolic Dish (PD) Concentrating Solar Power (CSP) system is technically feasible and economically justifiable. Therefore, the primarily aim of this study is to carry out the fundamental investigation on the feasibility of solar CSP, focusing on PD type in Malaysia environment. To accomplish the aim, the 25kW PD model has been developed by using Matlab Simulink and by considering the tropical environment in Malaysia. This study has outlines the parameter that's used for 25kW PD system. Solar to electric efficiencies, annual energy, capacity factor, and Levelized Cost of Electricity (LCOE) were analyzed to determine the feasibility of the 25kW PD system under Malaysia environment. This study is covering a few regions in Peninsular Malaysia that are George Town, Kuantan, Subang, Senai and Kuching in East Malaysia. The result from this study shows that operating hours for PD system under Malaysia environment start to operate when solar irradiance 223 W/m2. Therefore, the total days for the PD system to operate in five locations in Malaysia are ranging from 84 to 57 days in a year. Meanwhile, there is a strong relationship between power output, capacity factor, and LCOE. With low power output and capacity power obtained from this study, thus it led to high LCOE. Therefore, this study has revealed the technical and economic analysis of the PD system under Malaysia environment. From the analysis, it shows that the PD system is feasible in term of technical but not economically feasible.Â Â